2002
DOI: 10.1002/1522-2683(200203)23:5<799::aid-elps799>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as signal amplification reagents for bioassays in microfluidic channels

Abstract: Liposomes with encapsulated carboxyfluorescein were used in an affinity-based assay to provide signal amplification for small-volume fluorescence measurements. Microfluidic channels were fabricated by imprinting in a plastic substrate material, poly(ethylene terephthalate glycol) (PETG), using a silicon template imprinting tool. Streptavidin was linked to the surface through biotinylated-protein for effective immobilization with minimal nonspecific adsorption of the liposome reagent. Lipids derivatized with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Fluorescence-based assays have utilized microcapillary columns [417,[425][426][427] or microfluidic channels [415,428,429] coated with reporter molecules for target immobilization and formation of a sandwich complex with liposomes. Alternatively, complexes have been formed on the surface of a magnetic microparticle prior to immobilization in the channel using a magnet [430][431][432].…”
Section: Liposomes As Optical Labelsmentioning
confidence: 99%
“…Fluorescence-based assays have utilized microcapillary columns [417,[425][426][427] or microfluidic channels [415,428,429] coated with reporter molecules for target immobilization and formation of a sandwich complex with liposomes. Alternatively, complexes have been formed on the surface of a magnetic microparticle prior to immobilization in the channel using a magnet [430][431][432].…”
Section: Liposomes As Optical Labelsmentioning
confidence: 99%
“…The first MHI example is an electrokinetically operated microfluidic heterogeneous bioassay which adsorbed the rabbit immunoglobulin G (rIgG) continuously in a microchannel by immobilizing the protein A (PA) on the channel inner surface (Dodge et al 2001). From then on, a lot of research has been reported to demonstrate the applicability of the MHI for the enrichment and purification of various analytes (Burg et al 2006;Eteshola and Leckband 2001;Eteshola and Balberg 2004;Furdui and Harrison 2004;Hu et al 2005;Linder et al 2002;Locascio et al 2002;Yakovleva et al 2002;Yang et al 2001). In addition to the experimental studies, some theoretical models and numerical simulations have been presented to guide the MHI design, including flow velocity selection and surface density optimization of the capture antibody (Lionello et al 2005;Zimmermann et al 2005).…”
Section: Introductionmentioning
confidence: 99%